Effect of γ-irradiation on structural, morphological and luminescence properties of cerium-doped Y3Al5O12 nano-material. Issue 9 (3rd October 2019) - Boukerika, Allaoua; Guerbous, Lakhdar
ABSTRACT: Cerium-doped yttrium aluminum garnet (YAG: Ce 3+ ) nanopowder phosphors have been elaborated by sol–gel process and annealed at 900°C for 2 h. The prepared phosphors were exposed to gamma radiation, using 60 Co source, at different doses ranging from 5 to 100 kGy. The influence of γ-irradiation on the structural, morphological and luminescence properties of YAG: Ce 3+ phosphors were investigated in detail by X-ray diffraction, ﬁeld emission scanning electron microscopy (FESEM), Fourier transforms infrared spectroscopy (FTIR) and photoluminescence measurements. The XRD analysis confirmed the presence of single cubic phase for all samples of YAG: Ce 3+ nanophosphors independent of γ-rays dose. FESEM micrograph results revealed that the particles present flate-like shapes and high density of dislocation for sample irradiated at 100 kGy of γ-ray. The YAG: Ce 3+ nanophosphors showed broad green–yellow emission band in the range of 450–700 nm with maximum intensity at 538 nm assigned to the 5d → 4f transitions of Ce 3+ ion. The emission intensity of YAG: Ce 3+ phosphors vary with the γ-ray irradiation and reach the maximum for sample irradiated to a dose of 25 kGy. The variation of luminescence intensity is related to the crystallite size and Ce 4+ ions content in YAG host nanomaterial.